Pembuatan zat warna alami dalam bentuk serbuk untuk mendukung industri batik di Indonesia - Paryanto Paryanto; Agus Purwanto; Endang Kwartiningsih; Endang Mastuti (Jurnal Rekayasa Proses, 2012)
Synthetic dyes are very practical to use and can lead to a striking color on the products. However, synthetic dye effluent may pollute the environment. For this reason, currently natural dyes have been used again for coloring. In order to ease the use of natural dyes, the liquid form of the dyes is dried into powder. In the present study, natural dyes extracted from kesumba seeds were dried using a spray dryer to form a powder. The Kesumba dye was extracted in an alkaline solutions of NaOH and Ca(OH)2. Drying was carried out with a feed having an average rate of 0.13 ml/sec at a temperature of 70°C. Meanwhile, dryer temperature was 120°C. Experimental results showed that extraction using NaOH solution offered better results than that using Ca(OH)2 solution. The extraction using NaOH solution was optimum at NaOH concentration of 0.4 M, temperature of 90°C and duration of 180 min. With this condition, the resulting powder was 19.6 g/L extract solution.